(untitled) (Current Problems in Rail Vehicles, 2025)
In connection with the modernization of the rack railway lines in Czechia and Slovakia in recent years (Štrba – Štrbské Pleso in 2021 and Tanvald – Kořenov in 2025), it was necessary to design and produce rack railway turnouts for these lines, which involved a thorough study of the current solution of such turnouts abroad and then designing own solution. The paper focuses on the currently designed turnouts for the Abt rack railway system, which is used on the modernized line Tanvald – Kořenov. In the paper the readers will be introduced to the types of the rack railway turnouts for the Abt system. Furthermore, the rack railway turnout solution of the Czech manufacturer of switches and crossings, DT – Výhybkárny a strojírny, a.s., is presented. Within the development of turnouts, much attention was also focused on the interaction of the turnout not only with the rack railway vehicle but also with the adhesion vehicle, with a focus on possible collisions. It was necessary to deal with the missing supporting documents, which was partially replaced by 3D scanning of the locomotive bogie components. In the paper, attention is also paid to the problem of the rack and cogwheel interaction.